Pengaruh Penambahan MasterGlenium ACE® 8595 dengan Pengurangan Kadar Air 37.5% dan Kadar Semen Rencana 409.80 kg/m3 Terhadap Kuat Tekan Beton - Andre Novan; Ermiyati Ermiyati; Yenita Morena; Ella Silvana Chebelita (Universitas Medan Area, 2022)
MasterGlenium ACE® 8595 is a Type F chemical that serves to reduce the amount of mixing water, improve workability and improve concrete quality. The purpose of this study was to find out the effect of adding MasterGlenium ACE® 8595 with a reduction in water content of 37.5% and a plan cement level of 409.80 kg / m2. The research was conducted in the laboratory using the DOE (Department of Environment) method in accordance with SNI 03-2834-2000 with a test object in the form of a concrete cylinder diameter of 150 mm and a height of 300 mm. MasterGlenium ACE® 8595 tested on concrete age 7 days 3 sample, and 28 days 5 sample. Variations in the dose of addition of MasterGlenium ACE® 8595 used 0.54%, 0.81%, 1.08%, 1.35%, 1.62%, 1.89% and 2.16% of cement weight. The test results of a strong concrete press normal at 28 days amounted to 29.77 MPa. The test results of a strong concrete press normal at 28 days amounted to 29.77 MPa. The results of the test are strong concrete press with the addition of MasterGlenium ACE® 8595 amounting to 51.61 MPa, 53.53 MPa, 45.95 MPa, 49.80 MPa, 41.25 MPa, 40.80 MPa, and 39.27 MPa. Based on the results of the test, the use of MasterGlenium ACE® 8595 in concrete will increase the strength of the press, workability, and age coefficient.